Enhanced Finite Element Numerical Analysis of Rigid Inclusion Lateral Resistance for Embankment on Slightly Overconsolidated Soft Clay - Kanti Haskarini; Agus Himawan; Masyhur Irsyam; Sugeng Krisnanto; Darmawan Adi Susanto; Bintang Putra Nusantara (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
Soft clay soils represent a significant challenge for embankment construction due to high compressibility, low shear strength, low bearing capacity, and excessive settlement potential. This study presents an enhanced finite-element model to evaluate the performance of Mortar Column Inclusion (Inklusi Kolom Mortar, or IKM) as a rigid inclusion supporting embankments over slightly overconsolidated soft clays, as implemented in the Serang-Panimbang Toll Road Project (STA 75+600 to STA 75+800). The propose approach integrates depth-dependent multilinear lateral resistance with structural “dummy” plate elements to capture soil arching within the Load Transfer Platform (LTP) and lateral column-soil interaction—an approach not previously applied in rigid inclusions modeling for soft clays. Studies on numerical modeling of IKM systems in slightly overconsolidated soft clays remain limited. Finite element analyses are conducted using PLAXIS 2D and 3D with axisymmetric, unit-cell, and plane strain approaches. The results show that the